Creation and pilot test results of the dermatology‐specific proxy instrument: the Infants and Toddlers Dermatology Quality of Life. (14th September 2018) - Chernyshov, P. V.; Boffa, M. J.; Corso, R.; Pustišek, N.; Marinovic, B.; Manolache, L.; Salavastru, C. M.; Tiplica, G. S.; Kakourou, T.; Alexopoulos, A.; Nasi, L.; Wojciechowska‐Zdrojowy, M.; et al.
Abstract: Background: Until now, there was no validated dermatology‐specific health‐related quality of life (HRQoL) instrument to be used in youngest patients. Objective: To create dermatology‐specific proxy instrument for HRQoL assessment in children from birth to 4 years. Methods: International focus groups, item selection and pilot tests were utilized. In order to avoid the problem of cross‐cultural inequivalence, focus group work and pilot tests were planned simultaneously in all national centres of the project. Comprehensibility, clarity, acceptance and internal consistency of new instrument were checked. Results: The title 'Infants and Toddlers Dermatology Quality of Life' was chosen for our new instrument with the proposed acronym 'InToDermQoL'. Focus group work was completed in seven national centres (Croatia, Germany, Greece, Malta, Poland, Romania and Ukraine). A total of 170 families of children with different skin diseases were interviewed, and a pilot version of the instrument was created. Centres from France, Denmark and Spain have joined the project at this stage. Parents of 125 children with skin diseases filled in the pilot versions of the instrument. Good comprehensibility, clarity, acceptance and internal consistency of the InToDermQoL were confirmed. The pilot test results showed that the InToDermQoL questionnaire well differentiates severity‐dependent differences. It was also checked and confirmed during the pilot test that no significant information was missed in the questionnaire. Three age‐specific versions of the InToDermQoL questionnaire with 10, 12 and 15 items, respectively, were approved for field tests. Conclusion: The pilot test results showed that the InToDermQoL questionnaire has good comprehensibility, clarity, acceptance and internal consistency and well differentiates severity‐dependent differences. Further validation of the InToDermQoL during international field test will be performed.